Effects of evergreen trees on mental restorative quality of winter landscapes - Zhao, Jingwei; Li, Xintao; Sha, Bingru (Journal of Environmental Engineering and Landscape Management, 2024)
Compared with other seasons, winter usually has low mental restorative quality due to the lack of greenness. Reasonably adding evergreen trees to winter landscapes can improve the quality. However, what proportion, species and planting site of evergreen trees are better for mental restoration? To address this question, two original pictures (describing two landscape types) and 24 manipulated pictures (including three categories and four grades of proportion of evergreen trees) were collected, and 381 respondents were employed to score the mental restorative quality of each picture. The results revealed that planting evergreen trees in the landscape with water was more efficient in promoting mental restoration than planting them in the landscape without water. Adding broad-leaved evergreen trees was much better than adding coniferous trees and the mixture of the two. And, for the landscape with water, moderate proportion of evergreen trees possessed significantly higher mental restoration than low or high proportion.